Relationship between Duffy Genotype/Phenotype and Prevalence of Plasmodium vivax Infection: A Systematic Review - Picón-Jaimes, Yelson Alejandro (2023)
The Duffy protein, a transmembrane molecule, functions as a receptor for various chemokines and facilitates attachment between the reticulocyte and the Plasmodium Duffy antigen-binding protein. Duffy expression correlates with the Duffy receptor gene for the chemokine, located on chromosome 1, and exhibits geographical variability worldwide. Traditionally, researchers have described the Duffy negative genotype as a protective factor against Plasmodium vivax infection. However, recent studies suggest that this microorganism’s evolution could potentially diminish this protective effect. Nevertheless, there is currently insufficient global data to demonstrate this phenomenon. This study aimed to evaluate the relationship between the Duffy genotype/phenotype and the prevalence of P. vivax infection. The protocol for the systematic review was registered in PROSPERO as CRD42022353427 and involved reviewing published studies from 2012 to 2022. The Medline/PubMed, Web of Science, Scopus, and SciELO databases were consulted. Assessments of study quality were conducted using the STROBE and GRADE tools. A total of 34 studies were included, with Africa accounting for the majority of recorded studies. The results varied significantly regarding the relationship between the Duffy genotype/phenotype and P. vivax invasion. Some studies predominantly featured the negative Duffy genotype yet reported no malaria cases. Other studies identified minor percentages of infections. Conversely, certain studies observed a higher prevalence (99%) of Duffy-negative individuals infected with P. vivax. In conclusion, this systematic review found that the homozygous Duffy genotype positive for the A allele (FY*A/*A) is associated with a higher incidence of P. vivax infection. Furthermore, the negative Duffy genotype does not confer protection against vivax malaria.